Warning from a pediatric patient with severe myositis ossificans combined with femoral fracture: a case report - Wang, Mengyao; Cao, Jin; Zhu, Huanye (Frontiers in Pediatrics, 2025)
Myositis ossificans (MO) is a self-limiting benign ossification disorder, characterized by heterotopic ossification within skeletal muscles. Pediatric MO cases are rarer, easy to be misdiagnosed. The diagnosis of traumatic MO is based on a thorough history, physical examination, and imaging studies. Early and proactive conservative treatment can often be effective. We report a case of a 6-year-old patient with a femoral fracture combined with severe MO. He was misdiagnosed at a community hospital as having a bone tumor combined with a pathological femoral fracture and was referred to our hospital. Upon examination, we found that his condition was unusual. The patient, a child taekwondo athlete, was injured during high-intensity training, and upon examination, severe MO was found around his hip area. Ultimately, he underwent minimally invasive surgery with elastic intramedullary nails for the femoral fracture, and we adopted a conservative treatment strategy for MO. After one year of follow-up, the patient recovered well with no signs of recurrence of MO. This case report highlights the health risks faced by child athletes during high-intensity training. Repeated muscle injuries can lead to MO, and in severe cases, complications such as fractures. When diagnosing traumatic MO, it is imperative to obtain a comprehensive history of prior trauma and muscle injuries. This information can facilitate differentiation of the condition from other diseases, such as osteosarcoma, especially in the absence of histological evidence. In the case, during a one-year follow-up, the affected limb of the patient showed good functional recovery with no recurrence of MO, demonstrating the effectiveness of surgical treatment for the femoral fracture and conservative treatment for MO.